Patologi Birokrasi Dalam Pelayanan Pemerintah (Studi pada Kantor Pertanahan Kota Cimahi) - Hamirul, Hamirul -; Hamirul, Hamirul (Jurnal Ilmu Administrasi Negara (JUAN), 2019)
Government functions in service are always criticized by various groups including the community and bureaucratic disease causes negative images for the government in terms of service, using descriptive methods with concurrent concurrent mixed method triangulation. The results of the research found in pathology which is the result of internal situations within the government environment are inadequate rewards and the following are some therapies that can be given at the Cimahi city BPN office, among others: To minimize the bureaucratic pathology in the Cimahi city BPN office is to create social conditions good, creating intelligent emotional, intellectual good intellectuals, creating good character and creating good spirituality; Officials in the BPN city of Cimahi should report on their wealth starting from the first position, and given ethical awareness, awareness of morality, increasing faith, feasibility of life, through social interaction, through openness, through education and training, through informal and formal groups.